2009
DOI: 10.1038/ki.2009.230
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase inhibition ameliorates experimental diabetic nephropathy

Abstract: Diabetic nephropathy is characterized by excessive extracellular matrix accumulation resulting in renal scarring and end-stage renal disease. Previous studies have suggested that transglutaminase type 2, by formation of its protein crosslink product epsilon-(gamma-glutamyl)lysine, alters extracellular matrix homeostasis, causing basement membrane thickening and expansion of the mesangium and interstitium. To determine whether transglutaminase inhibition can slow the progression of chronic experimental diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 31 publications
3
83
0
Order By: Relevance
“…Additionally, we recently reported that TGase2 is involved in diabetic vasculopathy resulting from apoptosis in endothelial cells and in the aorta, heart, and kidneys of diabetic mice (28). Another study using streptozotocin-induced diabetic rats demonstrated that TGase inhibition ameliorates the progression of diabetic nephropathy (33), suggesting the possible role of TGase2 in this disease. TGase2 is also associated with cataracts through cross-linking crystallins and vimentin (18,25).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we recently reported that TGase2 is involved in diabetic vasculopathy resulting from apoptosis in endothelial cells and in the aorta, heart, and kidneys of diabetic mice (28). Another study using streptozotocin-induced diabetic rats demonstrated that TGase inhibition ameliorates the progression of diabetic nephropathy (33), suggesting the possible role of TGase2 in this disease. TGase2 is also associated with cataracts through cross-linking crystallins and vimentin (18,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study comparing liver fibrosis progression and regression with the extent of collagen crosslinking in several mouse models demonstrated that TG2 does not significantly affect fibrosis in mice deleted of TG2 vs. wild-type controls (261). This may be different when TG2 activity is blocked in wild-type mice because the irreversible TG2 inhibitor NTU281 ameliorated the development of fibrosis and kidney failure in a model of diabetic nephropathy (133,134). Given that this inhibitor acts extracellularly, its antifibrotic effects are likely attributable to inhibition of TG2 crosslinking activity.…”
Section: Posttranslationally Modified Proteins Affect Cell Phenotype:mentioning
confidence: 99%
“…Another profibrotic protein involved in the interaction of cells with the ECM is basigin (CD147) (347). Finally, syndecan-4 and the cross-linking enzyme tissue transglutaminase are also involved in renal fibrogenesis (348)(349)(350). Nothing is known about such mechanisms in the kidney allograft.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Degradation of the interstitial matrix proteins is feasible as long as the interstitial ''scar'' is not highly organized (343). Inhibition of tissue-transglutaminase may be an interesting antifibrotic approach (350). Defining the point of no return in renal fibrosis and the interaction with renal regeneration are the important challenges for future studies.…”
Section: Resolution and Regression Of Renal Fibrosismentioning
confidence: 99%